Living with water: spatial mechanisms of coastal communities - Arnis Rochma HaranI,; Resza Riskiyanto,; Bangun I.R. Harsritanto,; Muhammad I. Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper introduces spatial characteristics of the built environment systems in coastal communities. People in Morosari, Demak, Central Java one of the societies that always have to deal with water as part of their everyday life. The way how peoples respond to sea tidewater in any situation gave new insight into sustainable urban design strategy. This study aims to explore various spatial mechanisms operated by the people to reveal how the system works together. We proposed that the exploration of various mechanisms done by people when living with water may bring the possibility to expand the discourse of spatial systems on water resiliency. This study used a qualitative method in collecting data through observation, interviews, and video recording. The analysis is carried out by exploring the everyday life of the community that considers water as part of the living system. This study found three spatial mechanisms in the coastal environment system held by people when dealing with the water: (1) everyday spaces separation based on reading nature, (2) plug-and-play operation carried out both in their domestic area and neighborhood, and (3) leveling control by the material system. The finding of this study also presents another form of water resiliency that is constructed by the spatial system in the coastal environment